Peristedion richardsi sp. nov. (Actinopterygii: Teleostei: Peristediidae) from Indonesian waters, with synonymy between Peristedion riversandersoni Alcock, 1894 and Peristedion nierstraszi Weber, 1913 - Kawai, Toshio (Zootaxa, 2016)
A new armored searobin, Peristedion richardsi sp. nov., is described on the basis of three specimens collected from the deep sea (485–600 m) off Java, Indonesia. This new species differs from the Indo-West Pacific congeners in having anterior edge of the 4th sensory pore of the rostral projection located anterior to the anterior edge of the premaxilla, perifacial rim prominent starting near anterior margin of lower jaw, spatulate rostral projection with very narrow interspace between both rostral projections, rostral projection width 1.33–1.73 in interspace between both rostral projections, and rostral projection with straight margin on medial side at base. It is clear that Peristedion nierstraszi Weber, 1913 is a junior synonym of Peristedion riversandersoni Alcock, 1894. In addition, a lectotype is designated for P. nierstraszi.